Chemical reactivity: teaching and learning problems and attempted solutions - Bapoo, Abdool Hamid (My University, 2016)
This thesis reports on school teaching and learning problems in the area of chemical re&ctivity and on an attempt to overcome some of these problems with an in-service course for teachers. rhase 1 of this research was a study of the conceptions of aspects of reactivity, rates of reaction and chemical equilibrium held by secondary school students. The nature and origin of the conceptual di:Eficltlties, i.n the above areas were investigated. The concepts of ret,ctivity and reactivity se.rd.e s are formally introduced at a standard 8 level. These concepts form a springboard for the understanding of more formal quantitative worl< done i.n rates of reaction and chemical equilibrium at a standard 10 level. Two multiple-choice questionnaires, a reactivity qUestionnaire and a i'a'Ceand (.,quilibrium qUestionnaire, were designed to probe for the nature and ori9i.n of views held )y st<mdard 8 & 10 students respectively. The views of both the standard 8 & 10 students on aspects of react~vity and reactivity series Were investigated using the reactivity ql.ltlstionnaire.The views of a sample of 'Jtandard 8 students were also probed during interview sessions conducted at selected schools. standard 10 students views about concepts related to aspects of rates of reaction and chemical equilibrium, were also investigated
A thesis submitted to the Faculty of Science, Unjversity of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy in Science. March 1995
Keywords: Chemistry--Study and teaching (Higher)--South Africa; Science--Study and teaching (Secondary)--South Africa; Chemical reactions